An opsin 5-dopamine pathway mediates light-dependent vascular development in the eye - Nguyen, Minh-Thanh T; Vemaraju, Shruti; Nayak, Gowri; Odaka, Yoshinobu; Buhr, Ethan D; Alonzo, Nuria; Tran, Uyen; Batie, Matthew; Upton, Brian A; Darvas, Martin; Kozmik, Zbynek; Rao, Sujata; et al. (Nature cell biology, 2019)
During mouse postnatal eye development, the embryonic hyaloid vascular network regresses from the vitreous as an adaption for high-acuity vision. This process occurs with precisely controlled timing. Here, we show that opsin 5 (OPN5; also known as neuropsin)-dependent retinal light responses regulate vascular development in the postnatal eye. In Opn5-null mice, hyaloid vessels regress precociously. We demonstrate that 380-nm light stimulation via OPN5 and VGAT (the vesicular GABA/glycine transporter) in retinal ganglion cells enhances the activity of inner retinal DAT (also known as SLC6A3; a dopamine reuptake transporter) and thus suppresses vitreal dopamine. In turn, dopamine acts directly on hyaloid vascular endothelial cells to suppress the activity of vascular endothelial growth factor receptor 2 (VEGFR2) and promote hyaloid vessel regression. With OPN5 loss of function, the vitreous dopamine level is elevated and results in premature hyaloid regression. These investigations identify violet light as a developmental timing cue that, via an OPN5-dopamine pathway, regulates optic axis clearance in preparation for visual function.
Keywords: opsiny; dopamin; membránové proteiny; Membrane Proteins; Light; Endothelium, Vascular; Vitreous Body; Dopamine Plasma Membrane Transport Proteins; světlo; Mice; Threonine; myši knockoutované; retinální gangliové buňky; Opsins; Retinal Ganglion Cells; threonin; proteiny přenášející dopamin přes plazmatickou membránu; zvířata; transportéry VIAAT; Dopamine; Eye; Mice, Knockout; Vesicular Inhibitory Amino Acid Transport Proteins; myši; cévní endotel; oči; sklivec; Animals